The Effect of Android Studio Application to Increase Adolescent Nutrition Knowledge (Universitas Negeri Semarang, 2021)
The number of Corona Virus patients in various parts of the world, including Indonesia, increases every day because the spread is relatively fast and difficult to detect. Optimal body defense is needed to prevent COVID-19. One of them is eating a balanced nutritious diet. The purpose of this study was to see the effect of the android studio application on adolescent knowledge about nutrition in preventing COVID-19—the research method used pre-experimental using One Group Pretest-Posttest Design. The population in this study were grade XI IPA SMA Negeri 12 Semarang students. The sampling technique used purposive sampling. The results of the statistical analysis with the Wilcoxon test found that the p-value was 0.000 ≤ 0.05. So it can be concluded that there is a significant influence before and after the intervention using the android studio application media. Therefore, this study proposes a technology based on the Android Studio application that can be used anywhere and anytime